Adverse reaction to metal debris with concomitant incidental crystalline arthropathy in hip arthroplasty - Edward J. Testa, BS; Brian J. McGrory, MD (Arthroplasty Today, 2017)
Adverse reaction to metal debris (ARMD) is a known cause of failed metal in hip arthroplasty. Diagnosis of this type of prosthesis failure may be difficult, and the hallmark is an abnormally elevated serum cobalt level. Concomitant diagnoses may also be present, such as infection, instability, and loosening, and this may confuse interpretation of abnormal laboratories. We present here, for the first time, 2 patients with ARMD and crystalline arthropathy. In each case, the patient chose surgery for ARMD, with resolution of symptoms and no recurrence of the crystalline arthropathy. We present these cases to alert the orthopaedist that crystalline arthropathy may be present at the same time as ARMD, but is likely not the primary cause of symptoms.